One-Way Street - Benjamin, Walter (Harvard University Press, 2016)
Presented in a new edition with expanded notes, this genre-defying meditation on the semiotics of late-1920s Weimar culture, composed of 60 short prose pieces that vary wildly in style and theme, offers a fresh opportunity to encounter Walter Benjamin at his most virtuosic and experimental, writing in a vein that anticipates later masterpieces